1994
DOI: 10.1007/bf01253968
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of oilseedBrassica napus germ plasm based on restriction fragment length polymorphisms

Abstract: Oilseed rape (Brassica napus) is an important oilseed crop worldwide. Cultivars have been developed for many growing regions, however little is known about genetic diversity inB. napus germ plasm. The purpose of the research presented here was to study the genetic diversity and relationships ofB. napus accessions using restriction fragment length polymorphisms (RFLPs). Eighty threeB. napus accessions were screened using 43 genomic DNA clones which revealed 161 polymorphic fragments. Each accession was uniquely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
95
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 16 publications
15
95
2
2
Order By: Relevance
“…Our selection encompassed the range of morphological forms that occur in this species and that are commonly used to divide it into three groups or subspecies: the oilseed crop B. napus ssp oleifera (represented by 26 accessions here), the Rutabaga B. napus ssp napobrassica or rapifera (represented by two accessions here), and B. napus ssp pabularis or pabularia (one accession: the asparagus kale). Molecular analyses confirmed that these three groups represent distinct gene pools (Song et al, 1988;Diers and Osborn, 1994). Our selection of oilseed accessions included both winter and spring types, which were shown to be differentiated gene pools (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006) and accessions from broad geographic origins, which was shown to correlate with the patterns of genetic diversity in this germplasm (Diers and Osborn, 1994;Chen et al, 2008).…”
Section: Plant Materialsmentioning
confidence: 69%
See 2 more Smart Citations
“…Our selection encompassed the range of morphological forms that occur in this species and that are commonly used to divide it into three groups or subspecies: the oilseed crop B. napus ssp oleifera (represented by 26 accessions here), the Rutabaga B. napus ssp napobrassica or rapifera (represented by two accessions here), and B. napus ssp pabularis or pabularia (one accession: the asparagus kale). Molecular analyses confirmed that these three groups represent distinct gene pools (Song et al, 1988;Diers and Osborn, 1994). Our selection of oilseed accessions included both winter and spring types, which were shown to be differentiated gene pools (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006) and accessions from broad geographic origins, which was shown to correlate with the patterns of genetic diversity in this germplasm (Diers and Osborn, 1994;Chen et al, 2008).…”
Section: Plant Materialsmentioning
confidence: 69%
“…Molecular analyses confirmed that these three groups represent distinct gene pools (Song et al, 1988;Diers and Osborn, 1994). Our selection of oilseed accessions included both winter and spring types, which were shown to be differentiated gene pools (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006) and accessions from broad geographic origins, which was shown to correlate with the patterns of genetic diversity in this germplasm (Diers and Osborn, 1994;Chen et al, 2008). Most of the cultivars (22 out of 29) were represented by a single genetically homogeneous line, which was obtained after several generations of selfing (Table 1).…”
Section: Plant Materialsmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, natural accessions of rapeseed from three divergent gene pools (Diers and Osborn, 1994;Becker et al, 1995;Qian et al, 2006) clustered together when compared with virtual rapeseed lines and parental species in principal component analysis. This indicates that the amount of variation in natural rapeseed is small compared with that in the parental species, and that there is great potential to widen the genetic base of natural rapeseed by using the parental species.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 25 accessions from 10 wild types and 14 accessions from 7 cultivated types of the B. oleracea cytodeme, on the basis of the classification proposed by Snogerup et al (1990), were collected from the Centre for Genetic Resources (CGN; Wageningen, The Netherlands), the Institute of Plant Genetics and Crop Plant Research (IPK; Gatersleben, Germany), the Universidad Politécnica de Madrid (UPM; Madrid, Spain), the University of California (UC; Davis, CA, USA) and Southwest University (SWU; China). Four accessions of B. rapa that represented genetic variants from two centres of origin of B. rapa (East Asia and Europe) and six accessions of B. napus that represented natural variants of rapeseed (two European winter, two Chinese semi-winter and two European spring rapeseed) were selected on the basis of studies of the evolution of B. rapa (Gó mez-Campo and Qian et al, 2003;Zhao et al, 2005) and analyses of genetic diversity in natural rapeseed (Diers and Osborn, 1994;Becker et al, 1995;Qian et al, 2006). A total of 156 virtual lines of rapeseed were developed from the 39 accessions of the B. oleracea cytodeme and from the 4 accessions of the B. rapa as described below.…”
Section: Plant Materialsmentioning
confidence: 99%